100 President Oral Presentation Pick: Prematurity Blunts Protein Synthesis in Skeletal Muscle of Neonatal Pigs Independently of Birth Weight. (30th November 2020) - Rudar, Marko; Naberhuis, Jane; Suryawan, Agus; Nguyen, Hanh; Fiorotto, Marta; Davis, Teresa A
Abstract: Postnatal growth failure reduces lean mass accretion and increases adiposity. Previously we showed that preterm birth impairs the feeding-induced stimulation of mechanistic target of rapamycin (mTOR), translation initiation, and protein synthesis in skeletal muscle of neonatal pigs. Considering that pig body weight can vary widely at birth, we wished to differentiate the effect of prematurity versus BW on these responses. Pigs delivered by caesarean section at preterm (103 d) or term (112 d) gestation were fed parenterally for 4 d. On day 4, all pigs were fasted for 4 h and were either fasted one additional hour or fed an elemental meal by oral gavage, yielding four treatment groups: preterm fasted, preterm fed, term fasted, and term fed. A flooding dose of L-[4- 3 H]Phe was injected into pigs 30 min after feeding (30 min before euthanasia). Preterm and term pigs were stratified according to birth weight such that preterm pigs with the highest birth weight were compared to term pigs with the lowest birth weight (n = 10–13 per group). Despite similar birth weight of pigs in these two subgroups, relative body weight gain of preterm pigs was 33% lower than term pigs (22.0 vs. 32.9 ± 1.6 g·kg -1 ·d -1, P < 0.001). Gastrocnemius protein synthesis increased after feeding in both preterm and term pigs, but the increase was 18% lower in preterm than in term pigs pigs (Table 1). Feeding-induced AKT phosphorylation and mTOR-dependent 4EBP1 and S6K1 phosphorylation mirrored the pattern in protein synthesis. These results suggest that prematurity (rather than low birth weight, which is frequently associated with preterm birth) perturbs mTOR activation and protein synthesis after feeding. However, it is unclear whether an inadequate response to feeding also underpins poor growth in intrauterine growth restricted piglets. Research was supported by NIH and USDA.